To the 60th anniversary of E. Zelmanov (Algebra and Discrete Mathematics, 2015)
On September 7, 2015, a distinguished mathematician, one of thefounders of our journal, Efim Isaakovich Zelmanov, turned 60. He wasborn in Khabarovsk, Soviet Union (now Russian Federation), while hismother grew up in the Ukrainian city Zhytomyr.